Effects of An Integrated Nutritional Health Intervention on Energy and Protein Intake in Under Five-Year Malnourished Children - Yani Maidelwita; Tukimin bin Sansuwito; Faridah Mohd Said (Fakultas Ilmu Keperawatan Universitas Indonesia, 2025)
Malnutrition is thought to be the cause of more than one third of all child deaths, despite being rarely cited as a cause. In Indonesia, 19.9% of the population is malnourished, which is a very high prevalence. To prevent and treat malnutrition in children, numerous strategies have been developed, including an integrated nutritional health intervention. This research aimed to determine the effectiveness of an integrated nutritional health intervention for the energy and protein intake of malnourished children under the age of five. This study had a quasi-experimental design with a pre- and post-test control group. The research took place in Padang City, West Sumatra Province, between August 2020 and February 2021. The study data were collected using a standardized questionnaire at baseline and six months after the intervention, utilizing a sample size of 140 people. The data were evaluated using dependent and independent t-tests between the study’s baseline and end line. The energy and protein intake variables showed a difference, indicating a significant increase in the score from the baseline to the end line (energy intake: difference-in-differences (DID) = 405.53, 95% confidence interval [CI] = 362.01–449.05, p = .000; protein intake: DID = 4.62, 95% CI = 3.79–5.45, p = .000). This study found that the integrated nutritional health intervention increased the energy and protein intake of malnourished children and had a substantial impact on reducing the prevalence of risk factors when adequate protein and energy intake was provided. Keywords: energy intake, integrated nutritional health intervention, malnourished, protein intake Abstrak Pengaruh Intervensi Terpadu Kesehatan Gizi terhadap Asupan Energi dan Protein pada Anak Balita yang Mengalami Gizi Buruk. Malnutrisi diperkirakan menjadi penyebab lebih dari sepertiga kematian anak di dunia meskipun jarang dikategorikan sebagai penyebab utama. Di Indonesia, 19,9% anak mengalami malnutrisi. Angka ini merupakan angka prevalensi yang sangat tinggi. Untuk mencegah dan mengatasi malnutrisi pada anak, berbagai strategi telah dikembangkan, termasuk intervensi kesehatan gizi terpadu. Penelitian ini bertujuan untuk mengetahui efektivitas intervensi kesehatan gizi terpadu terhadap asupan energi dan protein pada anak balita yang mengalami malnutrisi. Studi ini menggunakan desain kuasi-eksperimen dengan kelompok kontrol pre-test dan post-test. Penelitian dilakukan di Kota Padang, Provinsi Sumatera Barat, antara bulan Agustus 2020 hingga Februari 2021. Data penelitian dikumpulkan menggunakan kuesioner standar pada awal dan enam bulan setelah intervensi, dengan jumlah sampel sebanyak 140 orang. Data dianalisis menggunakan dependent dan independent t-test antara data awal dan akhir penelitian. Variabel asupan energi dan protein menunjukkan adanya perbedaan, yang mengindikasikan peningkatan skor yang signifikan dari awal hingga akhir penelitian (asupan energi: perbedaan selisih [difference-in-differences/DID]) = 405,53, confidence interval [CI] 95% = 362,01–449,05, p = 0,000; asupan protein: DID = 4,62, CI 95% = 3,79–5,45, p = 0,000). Hasil dari penelitian ini menemukan bahwa intervensi kesehatan gizi terpadu meningkatkan asupan energi dan protein pada anak-anak yang mengalami malnutrisi dan memberikan dampak yang signifikan dalam mengurangi prevalensi faktor risiko ketika asupan energi dan protein yang memadai tersedia. Kata Kunci: asupan energi, asupan protein, intervensi kesehatan gizi terpadu, malnutrisi